Manifestation of tip burn on white cabbage hybrids of medium-late and late maturation - S. V. Koroleva; N. B. Shulyak (Овощи России)
Relevance. The most complex and common physiological disease on the cabbage is a tip burn, associated with impaired Ca2 + transport inside the plant. Of all the ways to control this physiological disease, the most effective is the cultivation of tolerant hybrids. Material and methods.The aim of the research was to evaluate the mid-late and late ripening F1 hybrids of white cabbage for a tip burn and to determine the degree of hybrids responsiveness to calcium deficiency depending on weather conditions. The studies were carried out at breeding and experimental plot of the vegetable growing department at All-Russian Rice Research Institute in 2017-2019 on drip irrigation. Material - hybrid combinations of ARRRI breeding.Results. The manifestation of a physiological disturbance called “burn of the top of the inner leaves of the cabbage head” or “tip burn” on individual hybrids was observed during all years of cultivation, but to a different degree; The greatest damage to the heads was recorded in the years (2017 and 2019) with high productivity, which is due to the intensive assimilation ability against the background of warm sunny weather. In 2019, the manifestation of burns was noted in 25% of hybrids, which allowed them to be divided into 4 groups, depending on the degree of damage and the spread of the disease.It was established that hybrids with overmature standing for 2.5-3 weeks and also hybrids that were promptly removed at the time of mass technical ripeness had a high degree of damage. The lines that are most often found in hybrid combinations with signs of burns (269-824, Agr1321, 269Jas13, Byum112, Yas25, etc.) were identified, but it is rather difficult to assume the nature of inheritance, and, therefore, to develop the principle of pair selection when developing relatively stable hybrids also not yet possible.